A comparison between the effectiveness of the ethanol based extract of pomegranate peel (Punica granatum) and simvastatin drug for lowering blood LDL level in hypercholesterolemic male rats (Rattus novergicus) - Pitra Mukhlis Wardani; Putrya Hawa (Faculty of Medicine, Universitas Islam Indonesia, 2015)
Background: Hypercholesterolemia is one of the major risk factors for coronary heart disease. Drugs of natural pomegranate peel extract using ethanol can be used as an alternative of simvastatin as standard drugs. Preclinical trials are needed before clinical trials in humans to ensure the efficacy of the drug from the nature. Objective: To compare effectiveness of pomegranate peel extract using ethanol (Punica granatum) with simvastatin for lowering LDL level in hypercholesterolemia white rats (Rattus novergicus). Methods: This study used an experimental research design with pretestposttest control group. We use 27 male hypercholesterolemia wistar strain rats were used as samples. The samples were divided into 3 groups. Group I as a negative control was given DMSO 2% 2ml/300gramBW, group II was given simvastatine 0.18 mg/200gramBB/day, group III was given ethanol extract of pomegranate peel 30mg/200gramBB/day for 15 days. Results: Results of paired t-test showed that the group treated with simvastatin decreased LDL levels significantly. The group treated with ethanol extract of pomegranate peel decreased LDL levels significantly. The group given the ethanol extract did not decrease LDL levels significantly. Conclusion: Extract of pomegranate peel using ethanol is not effective for lowering LDL levels in hypercholesterolemia white rats (Rattus novergicus) compared to simvastatin.